FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA BURUH PANEN BUAH KELAPA SAWIT(Studi Kasus Pada Divisi I PT. Megasawindo Perkasa IKecamatan Pelepat Kabupaten Bungo) - Fikriman Fikriman; Arif Herdiansyah (Universitas Muara Bungo, 2017)
Research conducted at the Division I Megasawindo PT Perkasa I Sub Pelepat Bungo on December 1, 2015 until January 1, 2016. Selection of the location of this research was done intentionally (purposive sampling) with the consideration that Division I had a workforce of most on the harvesting of coconuts oil with 79 workers to harvest. This study was conducted to determine the factors that affected the productivity of harvest labor of Oil palm fruit in the Division I PT.Megasawindo Mighty I Sub Pelepat Bungo. The data collection method used in the study was documentation technique that was to obtain data directly from the data of research that palm fruit harvest workers at the Division I PT.Megasawindo Perkasa District of Pelepat many as 79 workers harvest the palm fruits. But the workers must studied the labor of its work effectively during the year 2014 as many as 39 people. The results showed that the average labor productivity of oil palm fruit harvest workers amounted to 37.31 tons / person / month. Harvest Labor productivity of the palm fruits together significantly affected by factors of wages, work experience, number of dependents and age, it could be seen from the calculated F value (983.312)> F table (2.649), but the partial factor wages were on a very real effect on the productivity of harvest labor of the palm fruits, as seen from the value of 49 997 t> t table 2,032. While working experience factor, number of dependents and the age factordid not significantly affected harvest labor productivity of oil palm fruit division I PT. Megasawindo Mighty I Sub Pelepat Bungo.Keywords: Productivity, Labor harvest, factors and Palm Oil